1997
DOI: 10.1021/ma961731f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fullerenation of Polycarbonate via Simple Polymer Reactions

Abstract: Direct fullerenation of polycarbonate (PC), a commercially important optical polymer, is achieved by simply irradiating a solution of PC and C60 at room temperature using a conventional UV lamp or by warming up a C60/PC solution to a moderate temperature (60 °C) in the presence of AIBN, a typical radical initiator. The extent of fullerenation is controllable by varying the C60 feed ratio, and a fullerenated PC with a C60 content as high as 6.3 wt % (or more than two C60 molecules per PC chain) is readily prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 23 publications
4
59
0
Order By: Relevance
“…The hyperbranched poly(aryleneethynylene)s consist of clusters of aromatic rings and it was thought that they may exhibit optical limiting properties 27–30. This was proven to be the case.…”
Section: Resultsmentioning
confidence: 99%
“…The hyperbranched poly(aryleneethynylene)s consist of clusters of aromatic rings and it was thought that they may exhibit optical limiting properties 27–30. This was proven to be the case.…”
Section: Resultsmentioning
confidence: 99%
“…We have developed simple polymer reactions with general applicability for directly attaching C 60 to preformed polymers [15,16]. Polyacetylene is a prototypical conjugated polymer, and substituted polyacetylenes have been found to possess interesting material properties such as optical activity and liquid crystallinity [17±20].…”
Section: Introductionmentioning
confidence: 99%
“…The transmitted fluence, however, starts to deviate from the linearity at an incident fluence of w250 mJ/cm 2 and reaches a saturation plateau of w140 mJ/cm 2 . The optical limiting performance of hb-P(18/ IV) is superior to that of C 60 , a well-known optical limiter [53,54]. Taking into account that C 60 is a three-dimensionally p-conjugated buckyball, it may be concluded that the threedimensionally p-conjugated electronic structure of the hb-PArPs is responsible for their optical limiting properties.…”
Section: Propertiesmentioning
confidence: 99%